"Every One of Us Is a Strand in That Basket": Weaving Together Stories of Indigenous Wellness and Resilience From the Perspective of Those With Lived and Living Experience With HIV/Hepatitis C Virus. (20th March 2022) - Heidebrecht, Luke; Iyer, Subhashini; Laframboise, Sandy Leo; Madampage, Claudia; King, Alexandra
Abstract: This article primarily focuses on the stories shared by Indigenous women with living and/or lived experiences of HIV/hepatitis C virus from the Vancouver Downtown East Side who attended the "Awakening our Wisdom" retreat. Weaving together the story of an Indigenous approach to research that informed the design of the retreat and the findings that emerged, a basket is formed that highlights the ways settler-colonialism within Canada has produced a system of health care that has neglected the Indigenous experience. The emerging themes of Connection, Disconnection, and Reconnection offers teachings for Indigenous journeys of resilience and wellness for those living with HIV/hepatitis C virus. These findings may help health care practitioners identify health care places and spaces that are in need of decolonization and offer, from an Indigenous perspective, the next steps forward for a health care system that promotes Indigenous engagement and retention in care.